Characteristics and relationship of periodontal disease with juvenile idiopathic and rheumatoid arthritis - Surena Vahabi; Abdolrahman Rostamian; Ghazaleh Baniebrahimi (Wolters Kluwer Medknow Publications, 2015)
Background: Rheumatoid arthritis (RA) is the most prevalent chronic inflammatory disease of the joints. It is correlated with periodontal disease due to similar factors that exist in both diseases. The present study assessed the relationship of periodontal disease with RA and juvenile idiopathic arthritis (JIA). Materials and Methods: In this case-control study, 30 RA and 30 JIA patients along with similar number of matched controls were selected among patients referred to Imam Khomeini Hospital, Tehran, Iran. Periodontal parameters including pocket depth (PD), clinical attachment level (CAL), O'Leary and Bay plaque index (PI) and bleeding on probing (BOP) were determined in cases and controls. Erythrocyte sedimentation rate, number of painful and inflamed joints and severity of disease were evaluated in RA and JIA patients. Mann-Whitney U-test nonparametric, Spearman and Pearson's correlation coefficients, and Chi-square tests were used as statistical analysis (α = 0.05). Results: PD (4.17 vs. 3.6 mm; P < 0.0001), CAL (4.89 vs. 4.18 mm; P < 0.002), percentage of sites with PD >4 mm (58.83% vs. 44.33%; P < 0.002), percentage of sites with CAL >3 mm (74.13% vs. 64.4%; P < 0.001), percentage of sites with BOP (9.67% vs. 6.87%; P < 0.0001) and PI index (85.73% vs. 80.63%; P < 0.0001) were significantly higher in RA patients than controls. In this group, direct and significant correlations were found between serologic findings, disease severity and number of painful and inflamed joints with periodontal factors. In JIA patients, no significant relationships were found between JIA findings and periodontal parameters. Conclusion: Considering the limitations of this study, there was a relationship between RA and periodontal disease. Severity of periodontal disease increases in patients with RA, while no increased risk of periodontal disease or its severity was observed among JIA patients.